Optimal combinations of systolic and diastolic blood pressure in Korea: A nationwide population‐based cohort study - Won‐Jun Choi; Hye‐Sun Lee; Jung Hwa Hong; Hyuk‐Jae Chang; Ji‐Won Lee (The Journal of Clinical Hypertension, 2021)
Abstract We investigated the optimal combinations of systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels for lowest mortality in participants not taking hypertensive medication at the study baseline using nationwide representative databases. Survival rates and hazard ratios (HRs) were calculated using Kaplan‐Meier curves and multivariable Cox regression analyses. The discriminatory ability for clinical outcomes was assessed by Harrell's C‐index analysis. A survival spline curve was presented, and Classification and Regression Tree (CART) analysis was performed. SBP ≥ 140 group and DBP ≥ 90 group had the highest risk of mortality. Within SBP < 120, the HR (95% CIs) for all‐cause mortality (ACM) was the lowest for DBP 70‐79. Within SBP 120‐139, the HR (95% CIs) for ACM was significantly lower for DBP 70‐79. Within SBP ≥ 140, the HR (95% CIs) for ACM was significantly lower for DBP 80‐89. Conversely, within SBP ≥ 140, DBP < 70 showed the highest risk for ACM. Similar relationships were observed when survival spline curves and CART analysis were used. The combination of SBP and DBP discriminated better than SBP or DBP alone for mortality. The effect of DBP on mortality varies according to the SBP range. It is more effective to evaluate the effect of SBP and DBP jointly for clinical outcomes.